Evaluation of Thyroid Function Tests in Children with Chronic Liver Diseases - Ş. Şebnem Ön; Sezer Acar; Korcan Demir; Ayhan Abacı; Yeşim Öztürk; Sinem Kahveci Çelik; Ece Böber (Galenos Yayincilik, 2020)
Objective:Studies examining changes in thyroid function in the course of chronic liver disease have mostly been conducted in adults. The aim of this study was to investigate thyroid dysfunction in children with chronic liver diseases.Methods:Between 2005 and 2018, patients aged up to 18 years of age, diagnosed with chronic liver disease and had thyroid function test results available were included. Anthropometric characteristics, liver and thyroid function results were collected and analyzed.Results:The study included 107 (53 female; 49.5%) patients aged between one month and 18 years-old. Of the 107 patients, 96 (89.7%) had normal thyroid function results, seven (6.5%) had subclinical hypothyroidism (SH) and four (3.7%) had euthyroid sick syndrome. Of the patients with SH, one (14.2%) had glycogen storage diasease, one (14.2%) had biliary atresia, one (14.2%) had undiagnosed cholestatic liver disease, one (14.2%) had Alagille syndrome, one (14.2%) had idiopatic hepatitis, one (14.2%) had progressive familial intra-hepatic cholestasis and one (14.2%) had congenital hepatic fibrosis. Spearman correlation analysis showed a negative correlation between free tri-iodothyronine and direct bilirubin (r=-0.329, p=0.027).Conclusion:In conclusion, euthyroid sick syndrome or SH may affect up to 10% of children with chronic liver diseases. It is suggested that thyroid function should be evaluated in cases of pediatric chronic liver disease at diagnosis and during follow-up. Moreover, this study is the first to show a negative correlation between free T3 levels and direct bilirubin, suggesting a possible association between liver disease severity and thyroid function.